2009
DOI: 10.1002/jnr.22258
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic localization of neuroligin 2 in the rodent retina: Comparative study with the dystroglycan‐containing complex

Abstract: Several recent studies have shown that neuroligin 2 (NL2), a component of the cell adhesion neurexins-neuroligins complex, is localized postsynaptically at hippocampal and other inhibitory synapses throughout the brain. Other studies have shown that components of the dystroglycan complex are also localized at a subset of inhibitory synapses and are coexpressed with NL2 in brain. These data prompted us to undertake a comparative study between the localization of NL2 and the dystroglycan complex in the rodent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
4
3
0
Order By: Relevance
“…Mouse anti‐islet1 recognizes both Islet‐1 and ‐2 and has a well‐established pattern of cell labeling by IHC and in situ hybridization (ISH) in chicken motor and retinal neurons (Tsuchida et al,1994; Fischer and Reh,2002). The specificity of anti‐Lim1/2 antibodies was verified by IHC and ISH showing specific expression in only a subset of horizontal cells as previously reported (Tsuchida et al,1994; Lui et al,2010). Lim3 antibodies label bipolar cells by IHC equivalent to patterns observed by ISH (Tsuchida et al,1994; Zhadanov et al,1995; Ericson et al,1997; Glasgow et al,1997; Edqvist and Hallbook,2004; Edqvist et al,2006).…”
Section: Methodssupporting
confidence: 65%
See 2 more Smart Citations
“…Mouse anti‐islet1 recognizes both Islet‐1 and ‐2 and has a well‐established pattern of cell labeling by IHC and in situ hybridization (ISH) in chicken motor and retinal neurons (Tsuchida et al,1994; Fischer and Reh,2002). The specificity of anti‐Lim1/2 antibodies was verified by IHC and ISH showing specific expression in only a subset of horizontal cells as previously reported (Tsuchida et al,1994; Lui et al,2010). Lim3 antibodies label bipolar cells by IHC equivalent to patterns observed by ISH (Tsuchida et al,1994; Zhadanov et al,1995; Ericson et al,1997; Glasgow et al,1997; Edqvist and Hallbook,2004; Edqvist et al,2006).…”
Section: Methodssupporting
confidence: 65%
“…The specificity of anti‐Lim1/2 antibodies was verified by IHC and ISH showing specific expression in only a subset of horizontal cells as previously reported (Tsuchida et al,1994; Lui et al,2010).…”
Section: Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…Unlike Nrxn variants that are expressed in most excitatory and inhibitory neurons ( 43 ), the α-Nrxn-specific ligand Nxph1 is restricted to inhibitory interneurons ( 36 , 44 ), similar to αDAG, which also prefers subsets of inhibitory synapses where it may co-localize with Nlgn2 ( 45 48 ). Nxphs comprise a family of glycoproteins (Nxph1–4) that exhibit characteristics of secreted, preproprotein-derived molecules ( 35 , 36 ), but the structural determinants of their interaction with LNS2 ( 34 ) are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hoon et al concluded, that NL2 deficiency in the end causes a decrease of functionally intact GABA A receptors. Lui et al in 2010 showed that NL2 was also localized presynapically within the ribbon synapseactive zone complex of the photoreceptor terminals. In their results, NL2 was not associated with inhibitory GABAergic synapses in the OPL.…”
Section: Neuroligin 2 421 Nl2 Is Localized In the Retinamentioning
confidence: 99%